2011
DOI: 10.1183/09031936.00190310
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate markers predicting overall survival for lung cancer: ELCWP recommendations

Abstract: The present systematic review was performed under the auspices of the European Lung Cancer Working Party (ELCWP) in order to determine the role of early intermediate criteria (surrogate markers), instead of survival, in determining treatment efficacy in patients with lung cancer. Initially, the level of evidence for the use of overall survival to evaluate treatment efficacy was reviewed. Nine questions were then formulated by the ELCWP. After reviewing the literature with experts on these questions, it can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 148 publications
0
23
0
1
Order By: Relevance
“…In recent years, biostatisticians have proposed a wide variety of measures for validating surrogate endpoints [20,21]. Although tumor response and PFS are potential surrogate endpoints for OS in extensive-stage small cell lung cancer [22], their validity is controversial in advanced NSCLC [23]. Broglio et al recently focused on PPS, which they termed as survival post progression (defined as OS minus PFS), in a hypothetical clinical trial setting under the assumption that treatment affected PFS but not PPS [2].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, biostatisticians have proposed a wide variety of measures for validating surrogate endpoints [20,21]. Although tumor response and PFS are potential surrogate endpoints for OS in extensive-stage small cell lung cancer [22], their validity is controversial in advanced NSCLC [23]. Broglio et al recently focused on PPS, which they termed as survival post progression (defined as OS minus PFS), in a hypothetical clinical trial setting under the assumption that treatment affected PFS but not PPS [2].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of CTCs has not been well established for lung cancer; however, several studies have reported that the detection of CTCs may be a prognostic factor for lung cancer subsequent to surgical and chemotherapeutic treatment (17)(18)(19). Since NSCLC lacks validated biomarkers, a radiological response is recognized as a surrogate for survival or recurrence (20). CTC count may be an additional prognostic factor for survival, recurrence and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One issue is the lack of surrogate markers of antitumor activity that could provide an early indication of response to therapy and help guide clinical decision making (11). A second issue is the inherent difficulty in obtaining representative lung tumor specimens to explore and validate predictive tissue biomarkers of targeted therapies (12).…”
Section: Introductionmentioning
confidence: 99%